Effectiveness of proprioceptive training in athletes with and without ankle instability: systematic review - Silva , Guilherme Augusto Moreira; de Oliveira, Ruan Kaique; de Castro , Ana Maria; da Silva , Nathália Fernandes; de Oliveira, Bruna Almeida Pires Franco; Lino, Maria Eduarda Moreira; de Oliveira, Rodrigo Franco (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Background: The proprioceptive program is directly related to neuromuscular control, which uses proprioceptive afferences to provide dynamic stabilization of the joint. Some variables can be considered risk factors for injuries, such as sprains, sudden and unexpected movement activities, simple quick changes of direction, soil type or footwear, among others. The balance training program contributes to lower injury rates and increases sports performance rate. Thus works the perception and maintenance of postural balance from information coming from sensory afferences. Objective: To perform a systematic review and verify the effect of proprioceptive training on ankle joint in athletes. Methods: A search for clinical trials was performed in the PUBMED, WEB OF SCIENCE, PEdro and SCIELO databases, the terms used for the search were “Proprioception”, “Athletic” and “Rehabilitation”, with the filters: articles published between the years of 2015 to 2020 and research in humans. Only studies published in the English language that addressed the proposed theme were included. The PEDro scale was used to evaluate the quality of studies with clinical trials, where studies with a score lower than 6/10 on the scale were excluded. Results: With the search 69 articles were found, removing the duplicates we obtained 67 eligible articles, of these, 15 studies met the inclusion and exclusion criteria. After complete analysis, 9 studies were included. Conclusion: Proprioceptive training in athletes, lasting at least three weeks with weekly protocols composed of dynamic exercises directed at individuals with ankle instability is totally effective for both joint injury prevention and rehabilitation. In addition to the increase of variables such as postural balance, coordination, postural control and functional performance.